A Wireless Sensor Network System Using 6LoWPAN - Demir, Bilal; Ayrancioglu, Gokhan; Gezer, Cengiz; Gozuacik, Necip (Ieee, 2016)
Internet of Things is getting wide-spread attention since it became easily accessible with the low costs nodes. In a typical internet of things application, the data sensed by nodes is usually sent to a central device which collects the information and can act as a gateway towards other networks. In this way the data can be processed in order to command the actuators to perform special tasks. In such networks 6LowPAN together with RPL protocol can be used as an enabler technology. In this study we implemented a 6LowPAN network using Contiki operating system in order to collect information coming from different sensors residing in nodes and stored this information in a database to be accessed by Internet. In our 6LowPAN network nodes send UDP packets to a UDP Server located in a low cost rapid prototyping device.
6LoWPAN Kullanan Bir Algilayici Ag Sistemi
National Conference on Electrical, Electronics and Biomedical Engineering (ELECO) -- DEC 01-03, 2016 -- Bursa, TURKEY